Distinct patterns of surround modulation in V1 and hMT+ - Gorkem Er (NeuroImage, 2020)
Modulation of a neuron’s responses by the stimuli presented outside of its classical receptive field is ubiquitous in the visual system. This “surround modulation” mechanism is believed to be critical for efficient processing and leads to many well-known perceptual effects. The details of surround modulation, however, are still not fully understood. One of the open questions is related to the differences in surround modulation mechanisms in different cortical areas, and their interactions. Here we study patterns of surround modulation in primary visual cortex (V1) and middle temporal complex (hMT+) utilizing a well-studied effect in motion perception, where human observers’ ability to discriminate the drift direction of a grating improves as its size gets bigger if the grating has a low contrast, and deteriorates if it has a high contrast. We first replicated the findings in the literature with a behavioral experiment using small and large (1.67 and 8.05 degrees of visual angle) drifting gratings with either low (2%) or high (99%) contrast presented at the periphery. Next, using functional MRI, we found that in V1 with increasing size cortical responses increased at both contrast levels. Whereas in hMT+ with increasing size cortical responses remained unchanged or decreased at high contrast, and increased at low contrast, reflecting the perceptual effect. We also show that the divisive normalization model successfully predicts these activity patterns, and establishes a link between the behavioral results and hMT+ ​activity. We conclude that surround modulation patterns in V1 and hMT+ ​are different, and that the size-contrast interaction in motion perception is likely to originate in hMT+.